Influence of Innovative Economic Model on the Development of Cattle Breeding in Kazakhstan - MADENOVA, Kulshara M.; SHULENBAYEVA, Faya A.; BAUER, Maira Sh.; AGUMBAYEVA, Assiya Ye.; SAGINOVA, Balym K. (Journal of Advanced Research in Law and Economics; Vol 11 No 3 (2020): JARLE Volume XI Issue 3(49) Summer 2020, 2020)
Meet stockbreeding makes it possible to achieve significant progress in providing food to the country as a whole and thus ensure security and reduce dependence on imports of certain types of products. In Kazakhstan, this traditionally refers to the preservation of meat stock and, as a consequence, to the consumption of meat as the main type of carbohydrate and protein. The relevance of the study is in the formation of a sustainable system that would be the basis for a long-term temporary supply of meat products. The novelty of the study is determined by the fact that the formation of a sustainable economic model that allows for the increase in the number of meat breeds is based on the ability to ensure the growth of the feed base and reduce the share of imported feed. The authors determine the possibility of using the developed model for growing feed for meat stocks for the period of standard planning in economic development. The model is based on the prediction of cost-effective feed. The authors define wheat as a reference culture. The practical significance of the study is determined by the structure and share of imports in the preparation of the feed base and the possibilities of restricting the supply of feed and ready-made food additives as the basis for ensuring food security in the country.